2008
DOI: 10.1093/jb/mvn079
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinated Fibrinogen Inhibits Thrombin-catalysed Fibrin Polymerization

Abstract: Citrullination is the post-translational modification of arginine residues by peptidylarginine deiminases (PADIs). Fibrinogen is one substrate of PADIs under physiological conditions. Fibrinogen is an important factor for blood coagulation and inducing inflammation. The citrullinated form of fibrinogen appears in rheumatoid arthritis synovial tissue together with the production of autoantibodies that target self-peptides containing citrulline. However, whether the function of fibrinogen changes after citrullin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
2
28
0
1
Order By: Relevance
“…Given this seemingly global expression of PADs, some of which is apparently independent of disease states, it is likely that citrullinated proteins have many hitherto unknown non-pathological roles [2,5,36]. For example, citrullinated chemoattractants have been shown to reduce the extravasation of leukocytes as the citrullinated form of chemoattractants is unable to attract neutrophils [5,40e42] and citrullinated fibrinogen influences coagulation [43,44]. However, there are also many known pathological implications of citrullinated proteins other than RA.…”
Section: Discussionmentioning
confidence: 99%
“…Given this seemingly global expression of PADs, some of which is apparently independent of disease states, it is likely that citrullinated proteins have many hitherto unknown non-pathological roles [2,5,36]. For example, citrullinated chemoattractants have been shown to reduce the extravasation of leukocytes as the citrullinated form of chemoattractants is unable to attract neutrophils [5,40e42] and citrullinated fibrinogen influences coagulation [43,44]. However, there are also many known pathological implications of citrullinated proteins other than RA.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Nakayama-Hamada et al [16] reported that no FPA or FPB release and no polymerization of citrullinated fibrinogen were observed after thrombin stimulation. Moreover, they also demonstrated that citrullinated fibrinogen 8 and a synthetic peptide that mimics citrullinated FPA inhibit thrombin-catalyzed fibrin polymerization.…”
Section: Sds-page Conditions But Citrullinated Fibrinogen Did Not Unmentioning
confidence: 99%
“…Damaged cell products stimulate the retraction of endothelial cells, which facilitates the extravasation of fibrinogen and other plasma components (Méchin et al 2007). Citrullination can indeed occur within the rheumatoid synovial tissue with many different L-Arg residues citrullinated in different proteins including fibrinogen (Okumura et al 2009;Vossenaar 2004 (Nakayama-Hamada et al 2008). In addition, certain fibrinogen molecules can be converted to fibrin before deimination.…”
Section: Blood Clot Formationmentioning
confidence: 99%
“…The advanced degree of citrullination leads to denaturation of the protein (Tarcsa et al 1996a;Vossenaar et al 2003;Chang et al 2005;Nakayama-Hamada et al 2008). …”
mentioning
confidence: 99%